Targeted inhibition of the PTEN/PI3K/AKT pathway by YSV induces cell cycle arrest and apoptosis in oral squamous cell carcinoma - Lin Qiu; Qian Gao; Yiheng Liao; Xinxin Li; Cuiying Li (Journal of Translational Medicine)
Abstract Background Tyroservatide (YSV), a bioactive tripeptide, holds potential as an anti-tumor agent. However, its specific effects on oral squamous cell carcinoma (OSCC) have not been elucidated. This study aims to investigate the inhibitory effects of YSV on OSCC and explore the underlying molecular mechanisms. Methods A series of in vitro experiments were conducted to assess the impact of YSV on OSCC cell viability, colony formation, cell cycle, and apoptosis. RNA sequencing (RNA-seq), molecular docking, and western blotting were employed to investigate the molecular mechanisms. Additionally, a subcutaneous tumor model was established to validate the in vitro findings. Furthermore, PI3K inhibitors LY294002 and PI3K-IN-1, were used to confirm the role of the PTEN/PI3K/AKT pathway in YSV-mediated OSCC inhibition. Cell cycle and apoptosis were analyzed to assess the combined effect of YSV and LY294002. Results YSV significantly inhibited OSCC proliferation by inducing cell cycle arrest and apoptosis. RNA-seq and molecular docking revealed that YSV regulated the PTEN/PI3K/AKT signaling pathway. Western blotting confirmed the modulation of this pathway both in vitro and in vivo. The use of PI3K inhibitors, LY294002 and PI3K-IN-1, further validated the involvement of the PTEN/PI3K/AKT pathway in YSV-induced anti-tumor effects. Notably, the combination of YSV and LY294002 synergistically enhanced cell cycle arrest and apoptosis, demonstrating effective anti-tumor activity. In vivo experiments also supported these findings. Conclusion YSV inhibited the progression of OSCC by promoting cell cycle arrest and apoptosis through the regulation of the PTEN/PI3K/AKT signaling pathway. The combination of YSV and PI3K inhibitors, such as LY294002, exhibited enhanced anti-tumor activity, suggesting potential therapeutic strategies for OSCC treatment. Graphical abstract